IMPLEMENTASI KEBIJAKAN PELATIHAN KERJA DI DINAS TENAGA KERJA KOTA DEPOK TAHUN 2019-2021 - Dina Sari (2023)
This study aims to discuss how the implementation of job training policies at the Depok City Manpower Office in 2019-2021 uses the theory of public policy implementation. The method used in this study is descriptive qualitative using primary data sources and secondary data. Data collection techniques used in this study were interviews and literature studies in the form of books, news, and previous research journals relevant to this research. Researchers also used three stages of data analysis according to Miles and Huberman, namely data reduction, presentation/display data, and withdrawal/verification with data triangulation. The final results of this study indicate that the Manpower Office's choice to cooperate with LPK in implementing job training policies has been effective for the purpose of successful implementation of job training policies in 2019-2021. This success can be seen from the achievement of the performance targets given by the Mayor of Depok to the Manpower Office in carrying out the implementation of this policy, namely that as many as 200 workers must receive job training certificates. However, this choice turned out to have an impact on further delaying the construction of the UPTD BLK, in addition to that the construction of the UPTD BLK had apparently not been included in the RPJMD, in which all development policies were guided by this document. Keywords: policy implementation, work training, city of depok